Kemitraan Masyarakat Dalam Peningkatan Mutu dan Produksi VCO Mina Malole Rote Ndao - Muntasir, Muntasir; Dean, Muhajirin; Kolobani, Matias Nataniel; Purnasari, Cahyani; Upa, Fatmawati Pua (Jurnal Abdimas Multidisiplin, 2025)
Purpose: This community service program is designed to increase the quantity and quality of pure coconut oil production. through a partnership with Mitra Mina Malole. Methodology/approach: A participatory approach is implemented through training on VCO fermentation technology, mentoring on the use of appropriate tools, and regular implementation evaluations. The implementation team, comprising lecturers and students, collaborates directly with the partner community to transfer technology and monitor production outcomes. Results/findings: The community service program demonstrated an increase in production capacity, from 10–13 bottles per day to 20–25 bottles in 100 mL packaging, as well as improved product quality, resulting in a more hygienic and high-quality product. The product has obtained a P-IRT label and permit, and marketing has begun to expand, contributing to increased income and welfare for the local community. Conclutions: Community partnerships through appropriate technology and training have successfully improved the quality and production capacity of Virgin Coconut Oil in Ingguinak Village, increased family income, strengthened local business institutions, and expanded market access with more competitive and hygienic products. Limitations: The limited time for implementation means that ongoing support is still very much needed. Limited access to logistics and infrastructure in remote areas means that product distribution is not yet optimal. Contribution: This Program provides tangible socio-economic impacts for coconut farming communities. This program's recommendations can serve as a reference for developing broader community service policies and practices, supporting sustainable development, and strengthening local natural resource-based community economies.